Numerical thermal performance study in a heat exchanger tube with inclined elliptical rings - Sodsri, W.; Tamna, S.; Thianpong, C.; Promvonge, P. (My University, 2017)
The paper deals with a numerical study on the effect of inclined elliptical ring (IER) on heat transfer augmentation in a uniform heat-fluxed heat exchanger tube. In the present work, the 60° IER was mounted repeatedly in the tube with six different eccentricity ratios (ER = b/a = 1, 0.9, 0.8, 0.7, 0.6 and 0.5) at a single ring-pitch ratio PR = 1.0. Air as the test fluid flows into the tube for Reynolds number ranging from 4000 to 20,000. To find the optimum thermal performance, the effect of ER values on the heat transfer and pressure loss is investigated. The study indicates that the use of IER can induce higher turbulent intensity imparted to the flow leading to higher heat transfer in range of about 237 to 461% above the smooth tube.